1977
DOI: 10.1051/jphyscol:1977156
|View full text |Cite
|
Sign up to set email alerts
|

Size Dependent FMR Line-Shift and Line-Width Studies in Polycrystalline Ferrites and Garnets

Abstract: Rbumb.-Dans les phtnomenes de relaxation et de rtsonance dans les ferrites et grenats polycristallins, les contributions qui dtpendent de la dimension proviennent d'effets dus aux courants pelliculaires, aux inhomogenkites d'aimantation et aux defauts de surface ; au contraire Ies contributions indtpendantes de la dimension sont likes A I'anisotropie et A la porositt. Les contri

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Soft ferrites are most versatile because of their many technological applications [1][2][3][4][5][6][7][8]. It has been reported that in Mg-Mn ferrite if Fe ions are replaced by In [4,9,10], Al [1,4,10] and Co [11], the magnetic properties are modified.…”
Section: Introductionmentioning
confidence: 99%
“…Soft ferrites are most versatile because of their many technological applications [1][2][3][4][5][6][7][8]. It has been reported that in Mg-Mn ferrite if Fe ions are replaced by In [4,9,10], Al [1,4,10] and Co [11], the magnetic properties are modified.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the development of a technique by which the intrinsic g~ff value could be obtained in magnetic insulators with accuracies better than 2~. The effect of the eddy current and inhomogeneous demagnetisation fields in ferromagnetic resonance and relaxation was studied for the first time and a satisfactory explanation was offered for the size-dependence of the line-shift and line-broadening due to these two processes (Srivastava and Patni 1974;Srivastava et al 1977b). An exact solution technique for the determination of the dielectric and magnetic susceptibility of low loss microwave materials has been recently developed which helps to reduce substantially the high cost of the sophisticated instrumentation used presently in the techniques based on perturbation methods (Hanumanthrao and Patni 1978).…”
Section: Ferromagnetic Resonance and Relaxationmentioning
confidence: 99%